2016
DOI: 10.1136/bmjopen-2016-011632
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sodium-to-potassium ratio as a risk factor for stroke, cardiovascular disease and all-cause mortality in Japan: the NIPPON DATA80 cohort study

Abstract: ObjectivesTo evaluate the impact of dietary sodium and potassium (Na–K) ratio on mortality from total and subtypes of stroke, cardiovascular disease (CVD) and all causes, using 24-year follow-up data of a representative sample of the Japanese population.SettingProspective cohort study.ParticipantsIn the 1980 National Cardiovascular Survey, participants were followed for 24 years (NIPPON DATA80, National Integrated Project for Prospective Observation of Non-communicable Disease And its Trends in the Aged). Men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 33 publications
3
73
1
1
Order By: Relevance
“…Vegetable protein intake (continuous value) showed inverse relationships with mortality for almost all CVD subtypes irrespective of the presence of hypertension. We also observed significant relationual in this analysis 28,[30][31][32] . A limited number of nutrients were calculated in the NNSJ 90, and vegetable protein intake was not included 28) .…”
Section: Resultssupporting
confidence: 76%
“…Vegetable protein intake (continuous value) showed inverse relationships with mortality for almost all CVD subtypes irrespective of the presence of hypertension. We also observed significant relationual in this analysis 28,[30][31][32] . A limited number of nutrients were calculated in the NNSJ 90, and vegetable protein intake was not included 28) .…”
Section: Resultssupporting
confidence: 76%
“…We recruited healthy and hypertensive individuals in this study, since reducing Na/K ratio is essential for preventing hypertension and CVDs prior to clinical onset. 518 , 37 The main findings of this first study on self-monitoring Na/K ratio among healthy and hypertensive individuals included a trend towards larger reductions in urinary Na/K ratio observed in the intervention group. However, the effect of the self-monitoring device on the urinary Na/K ratio did not reach the accepted level of statistical significance on the pre-specified effect size (target reduction of 1 unit difference of Na/K ratio between intervention and control groups) under “pure self-management” (ie, without additional professional support) ( P = 0.088).…”
Section: Discussionmentioning
confidence: 89%
“…513 The Na/K ratio has also been reported to be a superior metric to either Na or K alone in relation to BP and incident hypertension 57 , 14 , 15 ; studies also report associations between Na/K ratio and CVD. 1618 The World Health Organization (WHO) plans to reduce Na intake and increase K intake in the future. 19 , 20 However, a conventional population approach does not seem sufficient 21 ; fairly large gaps exist between the actual intakes and the recommended target levels among populations.…”
Section: Introductionmentioning
confidence: 99%
“…A higher dietary Na/K ratio is a significant risk factor not only for incidence of hypertension and cardiovascular disease, but also for mortality from total and subtypes of stroke, cardiovascular disease, and all causes (29) . Our study found a greater mean Na/K ratio in total dishes, especially animal food-based dishes and fried rice with egg, prepared in restaurants vs. households, with the greatest difference of 24.8% found in egg fried rice.…”
Section: Discussionmentioning
confidence: 99%